Uma perspectiva pós-fordista na operação de sistemas elétricos - Garrofé, Paulo Henrique Simas (2004)
This work intends to show, through a case study, that the implementation of a production and work organization model based on process management could be seen through a post-Fordist perspective in the operation of power systems. Large brazilian companies in the power industry have adopted, since their creation, an organizational model based on management rules proposed by Henri Fayol, in a vertical and hierarchical structure fashion. On the other hand, the tasks performed in the control rooms of their Operation Centers follow the schemes established by Frederick Taylor's Scientitic Administration system and the principIes proposed by Henry Ford. Nevertheless, due to changes in the institutional model of the power industry that took place in the mid-nineties and the increasing awareness of society toward its rights along with the workers' urge for the democratization of social relations in their working environment, these power industry companies were driven to seek for fresher styles of management, more suitable for the new cultural, political, social and economic scenario. The System Operation Department in FURNAS decided to embrace, as a new form of production and work organization, a system based on process management, yet respecting the functional structure of the company, thus creating a matrix organizational structure. Notwithstanding, it has been observed that, depending on the implementation form and the adopted management mechanisms, this new system could be seen through a post-Fordist perspective in the operation activity of bulk power systems, typically carried out in Brazil by Fayolist companies, according to a Taylorist-Fordist perspective. To verify the outcome of this implementation, a research was carried out in alI tive Operation Centers of the System Operation Department in FURNAS Centrais Elétricas S.A., having as a key element the following characterization of the post-Fordist paradigm: integrated differentiation of production and work organization under the trajectory of technological innovation toward the democratization of social relations in enterprise-systems. The paper presents the perception both of the evolution in the workers' interpersonal relations and of the managerial actions taken to introduce this new system and shows the occurred changes regarding the democratization of social relations in the Department as well, among other factors which substantiate the research, whose results point to a new form of work and production management where these social relations tend to follow dialogical managerial actions that characterize the post-Fordist perspective.